Risk of Dementia Differs Across Lifestyle Engagement Subgroups: A Latent Class and Time-to-Event Analysis in Community-Dwelling Older Adults. (13th August 2021) - Moored, Kyle D; Bandeen-Roche, Karen; Snitz, Beth E; DeKosky, Steven T; Williamson, Jeff D; Fitzpatrick, Annette L; Carlson, Michelle C
Abstract: Objectives: Better understanding of the lifestyle activities shared among older adult subgroups may inform further health behavioral interventions that can be deployed at the group or community level. We applied latent class analysis to characterize qualitatively distinct lifestyle engagement groups, examined their differential risk of incident dementia, and compared their predictive utility to traditional activity frequency and variety scores. Method: Participants were from the Ginkgo Evaluation of Memory Study ( N = 3, 068, mean age = 78.5). Lifestyle activities were measured at baseline using the Lifestyle Activity Questionnaire. All-cause dementia was screened every 6 months and cases were clinically adjudicated. Median follow-up was 6 years. Time to dementia was assessed using discrete-time proportional hazards models, adjusted for demographic and health covariates. Results: Latent classes provided slightly poorer case discrimination than the frequency scores but identified distinct qualitative subgroups. In the 4-class model, the Variety (22%) and Intellectual (18%) lifestyle groups had high engagement in intellectual activities, whereas the Variety and Social groups (32%) had high engagement in formal social activities. Compared to the Least Active group (28%), the Variety (hazard ratio [HR] = 0.67, 95% confidence interval [CI]: 0.48, 0.93) and Intellectual (HR = 0.65, 95% CI: 0.45, 0.93) groups had significantly lower risk of incident dementia, but only among those without prevalent mild cognitive impairment. Discussion: Older adults highly engaged in intellectual activities, but not necessarily social activities, had the lowest risk of incident dementia. Activity frequency scores provided only slightly better case discrimination than activity variety scores and latent classes. Latent classes of older adults differed by their amount and types of activities, which may inform intervention design.